Does the basic farmland preservation hinder land transfers in rural China?. Issue 1 (25th September 2019) - Qiu, Tongwei; Luo, Biliang; Li, Shangpu; He, Qinying
Abstract : Purpose: The purpose of this paper is to assess the links between basic farmland preservation and land transfers in rural China. Design/methodology/approach: The Chinese provincial panel data from 2006 to 2016 were analyzed with the use of Arellano–Bond linear dynamic panel data estimations. Findings: The basic farmland preservation policy negatively affects the land transfer rate. In addition, this policy is most likely to limit land transfers between local acquaintances in the major grain-producing areas. Further evidence indicates that the basic farmland preservation policy has a negative impact on land rentals in general. Considering that land transfers such as exchanges and take-overs are excluded from rental transactions between acquaintances, the policy's constraints on land use are likely to hinder land rentals between acquaintances, which are market-oriented. Practical implications: Overall, this study's analysis suggests that the farmland preservation policy's constraints on land use rights are likely to result in a major diminishment of the rural rental markets. Under this policy, land that is designated as basic farmland cannot be converted to another use. However, it remains possible to improve the productivity of agriculture through other means. These possible avenues for improvement include enhancing the efficiency of production through expanding the scale of farming operations and developing the social services aspect of agriculture (i.e. the basic farmland preservation policy is likely to realize more social revenue than can be gained from land transfers). Thus, the arrangement of the basic farmland preservation policy in China can be managed in a way that is both economical and reasonable. Originality/value: To ensure food security, China has enacted several laws and regulations to preserve basic farmland, and it has promoted land transfers to improve farm productivity. Therefore, it is important to understand whether the basic farmland preservation policy restricts land use rights and hinders land transfers that could improve productivity. This study provides empirical evidence showing that the basic farmland preservation policy is actually not conducive to promoting land transfers and that it even discourages the market orientation of land rentals between acquaintances. In dealing with this issue, the Chinese Government should seek to balance the relationship between preserving basic farmland and promoting land transfers.